Outcomes in Patients with Cancer-Associated Venous Thromboembolism Receiving Immune Checkpoint Inhibitors: A Matched Cohort Study - Lage Bodour Danielian, Pedro Luiz; Dave, Heloni M.; Wei, Wei; Patel, Mehrie H; Angelini, Dana Elizabeth; Khorana, Alok A. (Blood, 2024)
Introduction: Cancer is a well-known risk factor for venous thromboembolism (VTE), accounting for about 20% of all VTE events and is associated with poor outcomes, including worsened survival. Cancer patients with VTE are at a greater risk of complications such as recurrent VTE and bleeding. Immune checkpoint inhibitors (ICIs) have revolutionized cancer treatment, but emerging data suggest an increased risk of VTE in cancer patients receiving ICI therapy. Outcomes of cancer-associated VTE may be different in patients undergoing ICI therapy. Identifying these associations is important, given that anticoagulation for cancer-associated VTE is often a fine balance between the risks of recurrent VTE and bleeding. We therefore conducted a cohort study to identify the incidence of recurrent VTE and bleeding in patients receiving ICI therapy compared to a cohort of matched patients receiving non-ICI systemic therapy. Methods: We conducted a retrospective cohort study at the Cleveland Clinic Cancer Center. Patients who developed VTE were identified in the electronic medical record (EMR) and categorized based on use of ICIs at the time of VTE. The comparison group of non-ICI-treated patients was matched by cancer type, stage, age, and sex. Outcomes were time-to-recurrent VTE (ttrVTE) and 6-month bleeding as identified in the EMR and adjudicated by manual review. Bleeding events were categorized as ISTH-defined major bleeding (MB) or clinically relevant non-major bleeding (CRNMB). For all statistical analyses, two-sided alpha was set at 0.05. ttrVTE was compared with the log-rank test, and rate of bleeding at 6 months was compared with Fisher's exact test. Results: A total of 222 subjects were included in this study. Of these, 138 (62.2%) were male, median age was 66 (interquartile range 59 - 73), 138 (62.2%) were current or former smokers, 143 (64.4%) had hypertension, 43 (19.4%) had diabetes, and 205 (92.3%) had distant metastases. The most frequent cancer sites were lung (43.2%), melanoma (17.6%), bladder (9.9%), and kidney (9.0%). The most frequently used ICIs were nivolumab (n=43, 38.7%), pembrolizumab (n=39, 35.1%), and combination of nivolumab and ipilimumab (n=14, 12.6%). 176 subjects died during follow-up (79.3%) and the median follow-up time for those alive was 46.4 months (range 1.0 - 103.3). 1-year recurrent VTE survival rate was 76% (66% - 87%) in the ICI group and 87% (95% CI 80% - 95%) in the non-ICI group (p=0.067). There were 35 bleeding events overall (15.8%), being 13 in the ICI group and 22 in the non-ICI group (p=0.44). None of the other factors (sex, race, smoking habits, body mass index, hypertension, diabetes, and extent of disease) were associated with recurrent VTE or bleeding. When analyzing bleeding classifications separately, the ICI group had an incidence of MB of 4.5% and the non-ICI group 9.9% (p=0.42). For CRNMB, the ICI group had an incidence of 7.2% and the non-ICI group 9.9% (p>0.99). Discussion: We found a substantial incidence of recurrent VTE and bleeding in cancer thrombosis patients. This could be explained in part by disease-related characteristics, such as a high proportion of patients with metastatic disease and a high proportion of lung and bladder cancer - which are known to carry a high risk of VTE. In our study, treatment with ICIs was not significantly associated with either recurrent VTE or bleeding. Future research is needed to elucidate the prognosis of cancer thrombosis patients receiving systemic therapy in effort to mitigate the risk of recurrent thrombosis and bleeding complications. No relevant conflicts of interest to declare.